THE MOTHER’S WISDOM IN LOUISA MAY ALCOTT’S LITTLE WOMEN - Christin Injilia Ratu,; Olga A. Rorintulus,; Agustine C. Mamentu, (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The aim of this study is to reveal Mother wisdom in Louisa May Alcott’s Little Women and to find out Mrs. March as a wise mother of her daughters. In this research, the writer used qualitative research and descriptive method, a research method that used non-numerical data to explain a phenomenon accurately. The writter cassified the sources of the data into two categories: They are primary and secondary sources. The primary source is thhe novel entitle Little Women by Louisa May Alcott and the secondary source are taken from books, artiicles, journal and internet data that related to the topic. In analyzing this research, the writer used objective approach, The results of the study show the wisdom of Mrs. March who plays the role of a mother in educating her children on the relationship between humans and God, human relationships with others, and human relationships with themself in Little Women by Louisa May Alcott.